Substitution therapy with amphetamine-isotherapic attenuates amphetamine toxicological aspects of addiction. (18th January 2019) - Segat, Hecson J.; Metz, Vinícia G.; Rosa, Higor Z.; Dias, Verônica T.; Barcelos, Raquel C.S.; Dolci, Geisa S.; Burger, Marilise E.
Graphical abstract: Highlights: Rats developed preference for and relapse to amphetamine (AMPH). The ultra-high diluted AMPH (successive dilutions of AMPH until 10 -24 mg/mL), was used for treat addiction parameters. Isotherapic reduced AMPH-induced relapse and anxiety behaviors. Isotherapic and AMPH changed dopaminergic molecular targets. Isotherapic per se reduced oxidative damage in prefrontal cortex of rats. Abstract: Introduction: amphetamine (AMPH) is related to development of addiction, anxiety-like behaviors and impairments of memory after chronic use. In the current experiment, an ultra-high dilution (10 −24 mg/mL) of AMPH was used, consisting of the AMPH isotherapic (AMPH-ISO), which can be used as a replacement therapy to treat AMPH addiction. Aim: To verify the inﬂuence of AMPH-ISO on toxicological aspects of AMPH addiction. Methods: Rats received d, l-AMPH (4.0 mg/kg, i.p.) in the conditioned place preference (CPP) paradigm (8 days). Then, half of each experimental group (AMPH or saline) received AMPH-ISO/vehicle (0.2 mL per rat, once a day), for fourteen days. On the fifteenth day, animals were re-assessed in the CPP paradigm (to verify relapse behaviors) after a single dose of AMPH (2.0 mg/kg). Subsequently, anxiety-like behaviors were quantified, followed by ex vivo assays in the pre-frontal cortex. Results: AMPH-ISO prevented relapse-like behavior of AMPH and reduced anxiety-like behavior per se in animals co-treated with AMPH. Molecular analysis evidenced that AMPH-ISO modulated dopaminergic targets (dopamine transporter, tyrosine hydroxylase and D1-R), whose immunoreactivity was increased by AMPH. Also, AMPH-ISO increased catalase activity and NPSH levels and reduced lipid peroxidation and protein carbonyl levels in the prefrontal cortex. Conclusion: This study shows that an ultra-high dilution of AMPH may be a useful alternative which can contribute with AMPH addiction treatment.